Emissions of Criteria Atmospheric Pollutants according to the Economic-Environmental Account in Ecuador from Stationary Sources (2008-2017) - Muela, Daniela; Viteri, Fausto (Journal of Environmental Accounting and Management, 2026)
In the present study, the quantification of criteria gas emissions was analysed according to the economic-environmental account of Ecuador from stationary sources during the period 2008-2017. The stationary sources considered were those involved in industrial, commercial, or service processes, as well as thermoelectric generation and oil refining. The criteria gases analysed were SO$_2$, NO$_X$, CO, NH$_3$, VOC, TOC, PM$_{10}$ and PM$_{2.5}$. The environmental economic account allows determining the reciprocal relationship of the environment (physical units) with the economy (monetary units), through stationary sources, as well as by economic sector (households, industries, and government). The different economic activities belonging to the different sectors were classified according to the International Standard Industrial Classification (ISIC). Emission factors (kg/m$^{3}$) approved by the environmental authority were used. In this way, results were obtained both in a disaggregated manner (by type of industry, type of pollutant and fuel used) as well as in an aggregated manner to obtain the total tons emitted by stationary sources. The criteria air pollutant, with the greatest contribution, from stationary sources was sulphur dioxide (SO$_2$), with a total of 1,088,462.35 tons emitted during the 2008-2017 period. Being the Industrial sector the main contributor to pollution, emitting 707,530.1 tons, specifically the economic activity related to Power Plants, its discharges represented 65 % of the total emissions of SO$_2$.